Metabolic Symbiosis‐Blocking Nano‐Combination for Tumor Vascular Normalization Treatment (Adv. Healthcare Mater. 17/2022). Issue 17 (7th September 2022) - Xiong, Hui; Liu, Xiaoyan; Xie, Zuohan; Zhu, Linyuan; Lu, Haipeng; Wang, Cheng; Yao, Jing
Abstract : Targeted Drug Delivery In article 2102724 by Jing Yao and co‐workers, blocking the metabolic crosstalk between tumor cells and tumor vascular endothelial cells through nano‐combination of LP and PP brings a new way to break through the predicament of tumor vascular normalization therapy. LP and PP are tacit companions to repair the tumor blood vessels.